Thermosensitive and cell-adhesive pluronic hydrogels for human adipose-derived stem cells - Park, Kwideok; Jung, Hong Hee; Son, Jun Sik; Rhie, Jong-Won; Park, Ki Dong; Ahn, Kwang-Duk; Han, Dong Keun (ASBM7: ADVANCED BIOMATERIALS VII, 2007)
Pluronic F127 has received increasing attention over many years as drug delivery systems, biomaterials, and hydrogels for tissue engineering. In this study, we synthesized temperature-sensitive and cell-adhesive triblock F127 copolymers, in which Arg-Gly-Asp (RGD) peptide ligand was grafted to Pluronic F127-4-methacryloxyethyl trimellitic anhydride (4-META) to obtain F127-META-RGD. The chemical structures of the F127-META-RGD block copolymers were confirmed by FTIR, H-1 and C-13 NMR, and GPC. The resultant F127-META-RGD showed very similar thermosensitive behaviors to F127 and 17127-META. The critical micelle temperature (CMT) of the F127 copolymers decreased in the order of F127 < F127-META < F127-META-RGD, whereas the particle size followed an opposite trend. Interactions between the F127 copolymers and adipose-clerived stein cells (ASC) were evaluated in terms of cell adhesion and proliferation on the hydrogel. These thermosensitive RGD-grafted Pluronic hydrogels that display the enhanced cell adhesiveness, are expected to be useful as a functional injectable scaffold for tissue engineering.